Museums in China: The Spatial Layout of Exhibition Halls and Its Impact on Visitor Experience - Zhang, Sijia; Hazim, Zulkarnain; Karim, Norashikin Abdul (Journal of Posthumanism, 2025)
This research question focuses on identifying how museum Exhibition Halls in China are laid out in terms of floor plans. The floor plan of a museum plays a crucial role in shaping the visitor experience and the overall effect of the exhibition, and a scientific spatial layout not only serves to create a good visiting environment but also helps visitors better understand the context of the exhibition and creates a space for experiencing it. This study conducted in-depth research on three museums in China, collected relevant data through observation and interview strategies, coded all the data in a unified way, and analysed the commonalities and found the differences in the floor plan layouts of each museum. This study aims to illustrate the specific impacts of museum floor plan layout on visitors’ experience, providing some reference value for the design of museums in China.